Regeneration of non-chimeric plants from DNA-free edited grapevine protoplasts - Scintilla, Simone; Salvagnin, Umberto; Giacomelli, Lisa; Zeilmaker, Tieme; Malnoy, Mickael A.; Rouppe van der Voort, Jeroen; Moser, Claudio (Frontiers in Plant Science, 2022)
The application of New Breeding Techniques (NBTs) in Vitis vinifera is highly desirable to introduce valuable traits while preserving the genotype of the elite cultivars. However, a broad application of NBTs through standard DNA-based transformation is poorly accepted by public opinion and law regulations in Europe and other countries due to the stable integration of exogenous DNA, which leads to transgenic plants possibly affected by chimerism. A single-cell based approach, coupled with a DNA-free transfection of the CRISPR/Cas editing machinery, constitutes a powerful tool to overcome these problems, maintain the original genetic make-up in the whole organism. We here describe a successful single-cell based, DNA-free methodology to obtain edited grapevine plants, regenerated from protoplasts isolated from embryogenic callus of two table grapevine varieties (V. vinifera cv. Crimson seedless and Sugraone). The regenerated, non-chimeric plants were edited on the downy- and powdery-mildew susceptibility genes, VviDMR6 and VviMlo6 respectively, either as single or double mutants.